Penerapan Persepsi Nasabah Terhadap Bank Syariah Indonesia - Rohmana, Devie Wianda; Nasrudin (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2023)
Bank Islam Indonesia operates in Indonesia on February 1 2021 in the field of sharia banking. This bank is the result of consolidation between Bank Mandiri Syariah, Bank BNI Syariah, and BRI Syariah. Towards the start of sharia banking activities, the government did not receive attention regarding the sharia banking framework. The examination results show that there are two types of customers in sharia banks; The main group is strict customers who choose banks because strict considerations trump other considerations, and the second type of customers are moderate Muslims, especially people who become customers because they consider the quality provided by sharia banks to be better than non-sharia banks. The recognition of Indonesian sharia banks in Indonesia is an extraordinary thing considering that the majority of Indonesian people are Muslims who are obliged to follow religious wisdom completely and not ignore what is forbidden in religion, such as ribawi. Exchange that occurs in a regular bank